Conceptual Boundaries regarding the Inventory Process in the Accounting System of the Republic of Moldova - Sargu, Nicu; Chira, Tatiana (The Journal of Accounting and Management, 2022)
This paper represents a theoretical approach of the role, importance, legality and methodology of the inventory process within the entity. The study of the topic in question is important because the results of the inventory provide information related to the existence and movement of the entity’s obligations to third parties for which the entity must provide a benefit or equivalent. Accounting is an information system used to quantify, process and transmit useful information for economic decision making. In the current conditions, it provides with objective and truthful information exposed in the Financial Statements, being accessible to all user groups, such as owners and employees, shareholders, creditors and investors, the tax service and other state bodies, etc.